Absence of the platelet receptor for drug-dependent antibodies in the Bernard-Soulier syndrome. - Kunicki, T J (1978)
The platelet membrane receptor for quinidine- and quinine-dependent antibodies was studied in three patients with the Bernard-Soulier syndrome (BSS) and in normal subjects with immunologic techniques based on the release of 51Cr from labeled platelets. The receptor could not be detected on BSS platelets but was present on platelets from each of 180 normal subjects. BSS platelets reacted normally with other allo- and autoantibodies. In confirmation of previous reports, BSS platelets were found to be deficient in glycoproteins Ib and Is. However, after apparently total cleavage of these proteins from the membrane of normal platelets by controlled hydrolysis with trypsin or chymotrypsin, 80% of the drug-dependent antibody receptor activity was retained. These observations suggest the existence of an additional, hitherto unrecognized membrane defect in Bernard-Soulier platelets.